Environmental factors influencing the risk of ANCA-associated vasculitis - Zhao, Wen-Man; Wang, Zhi-Juan; Shi, Rui; Zhu, Yu-Yu; Zhang, Sen; Wang, Rui-Feng; Wang, De-Guang (Frontiers in Immunology, 2022)
Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a group of diseases characterized by inflammation and destruction of small and medium-sized blood vessels. Clinical disease phenotypes include microscopic polyangiitis (MPA), granulomatosis with polyangiitis (GPA), and eosinophilic granulomatosis with polyangiitis (EGPA). The incidence of AAV has been on the rise in recent years with advances in ANCA testing. The etiology and pathogenesis of AAV is multifactorial and is influenced by both genetic and environmental factors, as well as innate and adaptive immune system responses. Multiple case reports showed that sustained exposure to silica in an occupational environment resulted in a significantly increased risk of ANCA positivity. A meta-analysis involving six case-control studies showed that silica exposure was positively associated with AAV incidence. In addition, exposure to air pollutants such as carbon monoxide (CO) is a risk factor for AAV. AAV also has seasonal trends. Studies have shown that various environmental factors stimulate the body to activate neutrophils and expose their own antigens, resulting in the release of proteases and extracellular traps of neutrophils, which damage vascular endothelial cells. In addition, the activation of complement replacement pathways may exacerbate vascular inflammation. However, the role of environmental factors in the etiology of AAV remains unclear and has received little attention. In this review, we summarized the recent literature on the study of environmental factors (such as seasons, air pollution, latitude, silica and microbial infection.) in AAV with the aim of exploring the relationship between environmental factors and AAV and possible mechanisms of action, so as to provide a scientific basis for the prevention and treatment of AAV.